1996
DOI: 10.1164/ajrccm.153.1.8542150
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of KL4-surfactant in preterm infants with respiratory distress syndrome.

Abstract: The present study was undertaken to determine if a synthetic peptide, KLLLLKLLLLKLLLLKLLLLK (KL4), in which K = lysine and L = leucine, in an aqueous dispersion of phospholipids (DPPC and POPG), would expand pulmonary alveoli and improve gas exchange in premature human infants with respiratory distress syndrome (RDS). The KL4 peptide was synthesized to resemble the amino acid pattern of surfactant protein B (SP-B). Forty-seven infants with RDS were treated within 4 h of birth with the KL4-peptide/phospholipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
1
4

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(85 citation statements)
references
References 24 publications
(11 reference statements)
1
79
1
4
Order By: Relevance
“…In summary, we have shown that the 21-residue peptide KL4 is a transmembranous helix with a mixed polar/nonpolar surface. The helix is oriented parallel to the lipid acyl chains and the structure and orientation of KL4 indicate that its mechanism of action is similar to that of SP-C, in contrast to previous suggestions [15][16][17][18]. This knowledge is useful for designing peptide analogues for further studies of the mechanism of action of pulmonary surfactant polypeptides.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In summary, we have shown that the 21-residue peptide KL4 is a transmembranous helix with a mixed polar/nonpolar surface. The helix is oriented parallel to the lipid acyl chains and the structure and orientation of KL4 indicate that its mechanism of action is similar to that of SP-C, in contrast to previous suggestions [15][16][17][18]. This knowledge is useful for designing peptide analogues for further studies of the mechanism of action of pulmonary surfactant polypeptides.…”
Section: Discussionmentioning
confidence: 75%
“…The small sizes of SP-B and SP-C have raised the possibility of producing bioactive analogues, for formulating synthetic peptide-containing surfactant preparations. Cochrane and Revak designed a 21-residue polypeptide, KL4, with a repetitive sequence of leucine and lysine residues [15][16][17][18]. This peptide mimics the pattern of hydrophobic and hydrophilic residues in SP-B and was supposed to stabilize the phospholipid bilayer by interactions with the lipid headgroups and superficial parts of the acyl chains [15].…”
Section: Introductionmentioning
confidence: 99%
“…Two important conceptual approaches being followed to develop synthetic exogenous surfactants are: (1) Combining human sequence recombinant proteins or synthetic amphipathic peptides with synthetic biological glycerophospholipids; and (2) combining synthetic amphipathic peptides with novel synthetic lipids designed to have favorable physicochemical properties such as high surface activity and structural resistance to inflammatory phospholipases during lung injury. Surfaxin® (KL4) [87,107,123,[189][190][191][192][193][194][195] and Venticute® (recombinant SPC surfactant) [26,[196][197][198][199][200][201] are two current examples of the first of these approaches (Table 3). However, the 21 amino acid KL4 peptide is only a very rough structural analog to native SP-B, and advances in peptide molecular modeling and synthesis technology support the feasibility of preparing new SP-B peptides with significantly greater sequence and molecular folding specificity, and correspondingly higher activity ( [202][203][204] for review).…”
Section: Examples Of Research On New Synthetic Exogenous Surfactamentioning
confidence: 99%
“…This surfactant has greater resistance to oxidation and peroxidation than beractant and was shown to improve pulmonary function in an animal model of RDS and a pilot study involving preterm infants with established RDS. [20][21][22] Lucinactant comes in a solution containing 30 mg of phospholipids per ml for a total recommended dose of 5.8 ml kg -1 or 175 mg of phospholipids. It requires warming to 44 1C followed by vigorous shaking and cooling to body temperature before administration.…”
Section: New-generation Protein-containing Synthetic Surfactantmentioning
confidence: 99%